Joint waveform and guidance control optimization by statistical linearisation for target rendezvous - Benavoli, Alessio; Balleri, Alessio; Farina, Alfonso (IEEE, 2021)
The algorithm proposed in this paper jointly selects the transmitted waveform and the control input so that a radar sensor on a moving platform can prosecute a target by minimising a predefined cost that accounts for the energy of the transmitted radar signal, the energy of a platform control input and the relative position error between the platform and the target. The cost is a function of the waveform design and control input. The algorithm extends the existing Joint Waveform Guidance and Control Optimization (JWGCO) solution to nonlinear equations to account for the dependency of the radar measurement accuracies on Signal to Noise Ratio (SNR) and, as a consequence, on the target position. The performance of the proposed solution based on statistical linearisation is assessed with a set of simulations for a pulsed Doppler radar transmitting linearly frequency modulated chirps.
Keywords: Cognitive rendezvous; adaptive waveform design; cognitive radar; Fisher Information Matrix (FIM); Cramér-Rao Lower Bound (CRLB); Linear Quadratic Gaussian control (LQG); Kalman Filter (KF); Joint Waveform and Guidance Control Optimization (JWGCO)